Observation of and study of the P-wave mesons *Supported in part by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (NSFC) (11335008, 11425524, 11625523, 11635010, 11735014), the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, the CAS Center for Excellence in Particle Physics (CCEPP), Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1532257, U1532258, U1732263), CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH003, QYZDJ-SSW-SLH040), 100 Talents Program of CAS, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG under Contracts Nos. Collaborative Research Center CRC 1044, FOR 2359, Istituto Nazionale di Fisica Nucleare, Italy, Koninklijke Nederlandse Akademie van Wetenschappen (KNAW) (530-4CDP03), Ministry of Development of Turkey (DPT2006K-120470), National Science and Technology fund, The Swedish Research Council, U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0010118, DE-SC-0010504, DE-SC-0012069), University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt. (March 2019) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ahmed, S.; Albrecht, M.; Alekseev, M.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, Y. 羽; Bakina, O.; Ferroli, R. Baldini; Ban 班, Y. 勇; et al.
Abstract: Studies of and the -wave charmed-strange mesons are performed based on an collision data sample corresponding to an integrated luminosity of 567 pb −1 collected with the BESIII detector at GeV. The processes of and are observed for the first time and are found to be dominated by the modes and, respectively. The Born cross sections are measured to be pb and pb, and the products of Born cross section and the decay branching fraction are measured to be pb and pb. For the and mesons, the masses and widths are measured to be, MeV, and MeV. The spin-parity of the meson is determined to be . In addition, the processes are searched for using the data samples taken at four (two) center-of-mass energies between 4.416 (4.527) and 4.575 GeV, and upper limits at the 90% confidence level on the cross sections are determined.